2022
DOI: 10.2337/dc21-1785
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glucose Metabolism and Glycemic Status With Once-Weekly Subcutaneous Semaglutide 2.4 mg Among Participants With Prediabetes in the STEP Program

Abstract: OBJECTIVE This analysis of 3,375 adults with overweight/obesity across the Semaglutide Treatment Effect in People with obesity (STEP) 1, 3, and 4 trials evaluated whether more participants with prediabetes had normoglycemia after 68 weeks’ treatment with once-weekly semaglutide 2.4 mg plus lifestyle intervention versus placebo and assessed changes in glucose metabolism in participants with prediabetes. RESEARCH DESIGN AND METHODS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…The reduction in fasting insulin and glucose with semaglutide is indicative of an increase in insulin sensitivity. Similar to the findings of other studies in the STEP trial program 7 , 27 , exploratory outcomes showed that in the semaglutide group 80% of participants with prediabetes at baseline reverted to normoglycemia by the end of the trial (compared with 37% of those receiving placebo), while 99% of participants with normoglycemia at baseline maintained normoglycemia at the end of the trial (compared with 86% with placebo). These findings suggest a potential beneficial effect of semaglutide on glycemic status, but whether semaglutide treatment delays or prevents progression to type 2 diabetes requires confirmation.…”
Section: Discussionsupporting
confidence: 84%
“…The reduction in fasting insulin and glucose with semaglutide is indicative of an increase in insulin sensitivity. Similar to the findings of other studies in the STEP trial program 7 , 27 , exploratory outcomes showed that in the semaglutide group 80% of participants with prediabetes at baseline reverted to normoglycemia by the end of the trial (compared with 37% of those receiving placebo), while 99% of participants with normoglycemia at baseline maintained normoglycemia at the end of the trial (compared with 86% with placebo). These findings suggest a potential beneficial effect of semaglutide on glycemic status, but whether semaglutide treatment delays or prevents progression to type 2 diabetes requires confirmation.…”
Section: Discussionsupporting
confidence: 84%
“…Although other pharmacologic treatments have been shown to be effective for type 2 diabetes prevention, including weight loss medications (orlistat and phentermine-topiramate), thiazolidinediones, α-glucosidase inhibitors, and even insulin glargine, the NCCC did not recommend them for diabetes prevention. A more recent study has also highlighted the potential role of glucagon-like peptide 1-receptor agonists for type 2 diabetes prevention ( 74 ). Because every kilogram of weight lost is associated with an additional 7% decrease in risk of progression to diabetes ( 14 ), newer treatments, including once-weekly glucagon-like peptide 1-receptor agonists and new dual receptor agonists such as tirzepatide, have great potential to reduce weight and prevent type 2 diabetes if rigorously demonstrated to be safe and effective for this indication.…”
Section: Resultsmentioning
confidence: 99%
“…HOMA-IR might also help to anticipate patient's response to incretin-based therapies. There is limited current evidence to establish whether HOMA-IR amelioration with GLP-1 is an independent outcome or a secondary result from weight loss and body recomposition (50,51). It is known that T2D is a chronic degenerative disease characterized by high risk of complications and an increasing social, economic and health burden worldwide (52,53); on the other hand, GLP-1 therapy is recognized as one of the key strategies to overcome clinical inertia in cardiorenal protection of T2DM patients (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…HOMA-IR might also help to anticipate patient’s response to incretin-based therapies. There is limited current evidence to establish whether HOMA-IR amelioration with GLP-1 is an independent outcome or a secondary result from weight loss and body recomposition ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%